Numerical modeling of dielectric barrier discharge plasma flow - Azizi, Bin Ahmadi (Universiti Malaysia Sarawak, (UNIMAS), 2013)
Dielectric Barrier Discharge (DBD) is a plasma actuator. A plasma actuator ,is a system or mechanism which produces plasma artificially. This discharge device has been used in wide range of industries, mainly in the environmental engineering industry. Most researches done are through experiments, but it does not obtain direct information on the distribution of the electric field and the electron density along the discharge axis. This information is important in order to optimize the plasma productio . In this study, the mathematical model of the DBD will be presented. Two models are required to model DBD plasma discharge mathematically; the electrostatics model and the fluid flow model. As for the electrostatics model, a model based on previous researches is adopted. And as for the fluid flow model, the Navier-Stokes equations are used to derive the model. In this study, it was noticed that the electrostatics model is time-independent. One of the characterisdcs of the DBD is that it performs under the alternating current, which is time-dependent. Hence, modification of the existing model is required, resulting in the development of the two systems: the spatial system and the spatial-temporal system. Both numerical results of the systems are implemented and analyzed. It is noticed that both systems produce similar results which indicates that the earlier formulated time-independent models actually is sufficient to model the problem. Then, the sensitivity fi analysis is conducted to certain DBD parameters in order. to study the performance of the DBD as a plasma actuator. This study concluded -that some parameters do affect the DBD plasma actuator.